(Im)possible dialogs between linguistic and literary studies / Diálogos (im)possíveis entre estudos linguísticos e estudos literários – interview with / entrevista com Beth Brait - Araújo, Everaldo Lima de; Silva, Jefferson Evaristo do Nascimento; Lenhardt, Jordana (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2018)
Elisabeth Brait is critic, essayist, associate professor in the University PUC São Paulo and retired associate professor of the University of São Paulo (USP). She graduated in Language and Literature, received her Doctorate degree in Linguistics and and Habilitation (professorship) in Linguistic at USP University and Post-Doctorate in École des Hautes Études in Sciences Sociales - Paris/France. She is a researcher Level 1 of CNPq, CAPES , CNPq and FAPESP advisor, study group leader of “Language, identity and memory” GP/CNPq/PUC-SP and creator/editor of the “Bakhtiniana” newspaper - Discourse study magazine (QUALIS A1/SCIELO/supported by CNPq and PUC-SP). Entrevista com Elisabeth Brait, crítica, ensaísta, professora associada da Pontifícia Universidade Católica de São Paulo (PUC-SP) e professora associada aposentada da Universidade de São Paulo (USP). Fez Graduação em Letras, doutorado em Linguística, Livre-Docência em Linguística na USP e pós-doutorado na École des Hautes Études en Sciences Sociales – Paris/França. É pesquisadora nível 1 do CNPq; Assessora da CAPES, do CNPq e da FAPESP; líder do GP/CNPq/PUC-SP Linguagem, Identidade e Memória; criadora e editora do periódico Bakhtiniana – Revista de Estudos do Discurso (QUALIS A1/SCIELO/Apoio CNPq e PUC-SP).